Successful salvage of a severe COVID-19 patient previously with lung cancer and radiation pneumonitis by mesenchymal stem cells: a case report and literature review - Huang, Xiaohua; Tan, Xin; Xie, Xiuwen; Jiang, Tingshu; Xiao, Yang; Liu, Zenghui (Frontiers in Immunology, 2024)
During the COVID-19 pandemic, elderly patients with basic diseases, such as tumors, had poor prognoses after progressing to severe pneumonia and often had poor response to standard treatment. Mesenchymal stem cells (MSCs) may be a promising treatment for patients with severe pneumonia, but MSCs are rarely used for patients with carcinoma. Here we reported a 67-year-old female with lung adenocarcinoma underwent osimertinib and radiotherapy and suffered from radiation pneumonitis. Unfortunately, she contracted COVID-19 and rapidly progressed to severe pneumonia. She responsed poorly to front-line treatment and was in danger. Subsequently, she received salvage treatment with 4 doses of MSCs, and her symptoms surprisingly improved quickly. After a lung CT scanning presenting with significantly improved infection, she was discharged eventually. Her primary disease was stable after six months of follow-up, and no tumor recurrence or progression was observed. MSCs may be an effective treatment for hyperactive inflammation due to their ability to immunomodulation and tissue repair. Our case suggests potential value of MSCs for severe pneumonia that is unresponsive to conventional therapy after COVID-19 infection. However, unless the situation is urgent, it needs to be cautious for patients with tumors. The safety in tumor patients still needs to be observed.